Randomized community trial to assess nutritional, socioeconomic, and health outcomes of a food forest initiative in Santa Elena Province, Ecuador: a study protocol - Faytong-Haro, Marco; Quijano-Ruiz, Alonso; Sanchez, Daniel; Alvarez-Munoz, Patricio; Gallegos-Caamaño, Stephanie; Yambay-Delgado, Victor; Checa, Karina; Delgado-Rendón, María José; Angulo-Prado, Andrea (Frontiers in Public Health, 2024)
Malnutrition is an escalating concern in low-and-middle-income countries (LMICs), including Ecuador, particularly within rural settings. To address this issue, food forests emerge as a promising intervention. This research protocol outlines a controlled intervention in the province of Santa Elena, aiming to evaluate the efficacy of a food forest in enhancing nutritional outcomes, with potential implications for broader replication. The study will be conducted in the Colonche Parish of Santa Elena Canton, where one commune will be randomly selected to receive the food forest intervention. In contrast, another similarly characterized commune, also randomly selected through cluster-based sampling, will serve as a control group, receiving no intervention. This randomized, comparative approach will enable a more precise assessment of the food forest's impact. Data collection will occur at three intervals: baseline, 6 months, and 12 months post-intervention. Comprehensive questionnaires will be employed to measure the food forest's influence on the communities' nutritional, economic, and health metrics, distinguishing between the intervention and control communes to elucidate the intervention's specific effects.